Praktik Transaksi Reksa Dana Syariah pada Aplikasi Bibit Perspektif Fatwa DSN-MUI NOMOR: 20/DSN-MUI/IV/2001 - Estri Isnaena; Nurlaeli, Ida (El-Uqud: Jurnal Kajian Hukum Ekonomi Syariah, 2024)
Encouraging healthy economic activity requires a capital market that provides a source of spending in the long term. So that investment in capital goods can lead to increased production of the producing labor market. Investment has become a muamalah activity that is recommended in Islamic teachings, so that platforms and applications that support investment activities have begun to emerge, such as the Bibit application. The Bibit application is one of the applications that provides mutual fund services and helps novice investors in starting an investment. This application also provides a choice of sharia mutual funds, in which there are several sharia investment startups. However, in-depth research is needed on the mechanism of sharia mutual funds through the application of Bibit perspective Fatwa DSN-MUI NUMBER: 20/DSN-MUI/IV/2001. This research uses a library research approach. The results of investment activities or investment in the capital market are activities carried out by property owners (shahibu al-maal) against issuers (company owners), with the aim of obtaining profits or expected profits.